Organizational trust among job seekers: The role of information‐seeking and reciprocation wariness. (1st June 2020) - Kedharnath, Uma; Shore, Lynn M.; Dulebohn, James H.
Abstract: This study explores job seekers' information‐seeking and pre‐hire trust, and the role of reciprocation wariness in the development of pre‐hire trust. Individuals seeking a job with a technology company ( N = 192) reported their perceptions of the organization's website usability and perceived similarity to their recruiter, organizational trustworthiness and trust, and intent to accept a job offer. Wariness moderated the relationship between website usability perceptions and trustworthiness. Unexpectedly, the interaction was in the opposite direction of what we predicted. In addition, job seekers' perceived similarity to their recruiter related to trustworthiness, and trust related to intent to accept a job offer. Our findings suggest that to some extent, recruiting organizations can encourage trust perceptions in the pre‐hire context.